Oor die toelating tot die Nagmaal - Pont, A. D. (HTS teologiese studies, 2001)
On being admitted to the Lord's Supper. In this study the mater of the invitation to the Holy Supper, in paricular the question of who may or should be invited, is discussed. A historical introduction precedes a discussion on the matter among Protestant churches 'n South Arica in light of the fact that children as young as age 6-7 are now being invited in the Dutch Reformed Church (NG Kerk), to participate 'n the Holy Supper. Special attenion is paid to the Caivinist tradition.